Partial Replacement of Ordinary Portland Cement in Concrete by Limestone Calcined Clay (LC2) - Abdelaziz, Merna (AUC Knowledge Fountain, 2025)
Limestone calcined clay (LC2) technique is a new approach that could address the environmental problem corelated with the construction industry due to its vital reliance on the ordinary Portland cement in its various applications. LC2 technique involves partial replacement of the OPC in concrete by limestone and calcined kaolinite clay with a ratio of 1:2 respectively. The main advantage of this technique is its high applicability due to its direct application on site. This study investigated the applicability of incorporating the LC2 technique in the construction industry. Three replacement percentages of OPC by LC2 in concrete were explored, which are 40%, 50%, and 60%. The objective of this study was achieved through evaluating the performance of the LC2 mixes in comparison with the OPC mix based on their mechanical properties, durability aspects, creep compliances, microscopic structures, and drying shrinkages. The LC2 mixes exhibited similar mechanical performance to that of the OPC mix except for the retarding effect in its strength gain during the first three days. Yet, there may be potential approaches that might improve this delayed early strength of the LC2 concrete. The LC2 mixes surpassed the control mix with respect to their moduli of elasticity. In addition, the LC2 mixes showed obvious superiority over the OPC mix in most of the durability and long-term deformation aspects including chlorides resistance, wet and dry cycles resistance, creep compliance, and drying shrinkage. The LC2 mixes proved its enhancement effect on the porosity refinement of concrete based on their microscopic structures. As the durability aspects of concrete are improved by increasing the LC2 replacement percentage while its mechanical performance is slightly compromised, 50% may be considered the optimum LC2 replacement percentage. Therefore, LC2 technique could be considered an effective approach for enhancing the sustainability of the construction industry in addition to improving the durability aspects of concrete.